2014
DOI: 10.1186/1471-2474-15-299
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of poor outcomes six months following total knee arthroplasty in patients awaiting surgery

Abstract: BackgroundIdentification of patients experiencing poor outcomes following total knee arthroplasty (TKA) before the intervention could allow better case selection, patient preparation and, likely, improved outcomes. The objective was to develop a preliminary prediction rule (PR) to identify patients enrolled on surgical wait lists who are at the greatest risk of poor outcomes 6 months after TKA.Methods141 patients scheduled for TKA were recruited prospectively from the wait lists of 3 hospitals in Quebec City, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 32 publications
1
44
0
Order By: Relevance
“…Hawker et al 20 noted that joint pain was the most common reason patients seeking TKA and, in contradiction to the findings of Lungu et al, 15 suggested that at a minimum, it seems reasonable that evaluation of the benefits of TKA incorporates improvement in pain. Hawker et al 20 aimed to determine the principle achievements of a 'good' outcome, defined as a clinically important improvement in pain and disability-assessed outcome using an overall measure of selfreported hip/knee pain.…”
Section: Painmentioning
confidence: 94%
See 1 more Smart Citation
“…Hawker et al 20 noted that joint pain was the most common reason patients seeking TKA and, in contradiction to the findings of Lungu et al, 15 suggested that at a minimum, it seems reasonable that evaluation of the benefits of TKA incorporates improvement in pain. Hawker et al 20 aimed to determine the principle achievements of a 'good' outcome, defined as a clinically important improvement in pain and disability-assessed outcome using an overall measure of selfreported hip/knee pain.…”
Section: Painmentioning
confidence: 94%
“…Lungu et al 15 aimed to develop a prediction tool that would allow the early identification of patients at risk of poor outcome following primary TKA. The best predictive model developed in this study incorporated five items from the baseline WOMAC questionnaire, specifically questions regarding function and stiffness.…”
Section: Joint Factors Functionmentioning
confidence: 99%
“…Risk calculators, appropriateness tools and predictive models have been developed to predict clinical outcomes and revision surgery, but these instruments lack the ability to provide precise thresholds that reliably predict failure and have not been validated using external datasets . Early efforts using large administrative datasets in the United States to develop a predictive tool of 30‐day readmission rates have had some success .…”
Section: Patient Characteristics Influencing Decision Makingmentioning
confidence: 99%
“…The minimal difference in falls and fracture risk between people who have undergone a THA and TKA is notable from this dataset. Whilst a good recovery following THR has been widely considered to be high in this population [29], between 20% to 30% of people following TKA still present with residual pain, loss of motion and functional difficulties at 12 and 24 post-operative months [30,31]. Since these are all recognised risk factors to falls, the minimal difference between the cohorts is an interesting finding which may or may not be representable of the wider population.…”
Section: Total Knee Arthroplastymentioning
confidence: 99%